Preharvest and postharvest intervention strategies to reduce prevalence of pathogens in beef and beef products - Ransom, Justin Robert, author; Sofos, John, advisor; Belk, Keith, advisor; Smith, Gary, committee member; Salman, Mo, committee member (Colorado State University. Libraries, 2004)
Studies were conducted to determine the prevalence of Escherichia coli O157:H7 in fecal and hide samples from cattle in feedlots and on their carcasses at slaughter plants. Prevalence in pens (lots) ranged from 0 to 78% positive in feedlot pen-floor fecal samples, and from 0 to 5% on carcasses from those lots immediately after final intervention; however, too few positive samples were isolated from carcasses to develop a strong relationship between E. coli O157:H7-positive fecal samples and E. coli O157:H7-positive carcass samples. Nonetheless, data suggested that pens having 20% or more E. coli O157:H7-positive feedlot-floor fecal samples also had 22.5% hide, 46.3% colon, and 12.5%, 2.5% and 0.6% positive carcass samples at pre-evisceration, post-evisceration and after final intervention, respectively. Conversely, feedlot-floor samples that were less than 20% positive were associated with 5.7% hide, 7.1% colon, and 7.1%, 0% and 0% positive carcass samples at pre-evisceration, post-evisceration and post-final intervention, respectively. A second study showed that preharvest pathogen mitigation strategies could aid in reducing prevalence of E. coli O157 in fecal and hide samples, as all treatments (i.e., Lactobacillus acidophilus-probiotic, neomycin sulfate-antibiotic and a prototype E. coli O157:H7 vaccine) resulted in fewer E. coli O157:H7 positive fecal and hide samples compared to controls. Although there was a significant lack of power, results from a preliminary antibiotic susceptibility study showed that there were no differences in antimicrobial resistance patterns between E. coli O157 isolates recovered from cattle treated with nothing versus those treated with neomycin sulfate before harvest. Finally, a series of studies comparing activated lactoferrin (2%) with nonactivated lactoferrin (2%), lactic acid (2%) and water were conducted to determine their effectiveness in reducing and/or inhibiting E. coli O157:H7, Salmonella Typhimurium and Listeria monocytogenes populations on bologna and fresh beef products. Results from these studies showed that activated lactoferrin and lactic acid were effective in reducing initial populations and inhibiting growth of E. coli O157:H7 and L. monocytogenes during storage of bologna. Additionally, when activated lactoferrin and lactic acid were sequentially applied to beef adipose tissue, their effectiveness in reducing and inhibiting E. coli O157:H7, L. monocytogenes, and S. Typhimurium populations was enhanced.
Keywords: livestock; microbiology; animal sciences